ARMA: rocking chair / Muhammad Fuad Abdul Rahman - Abdul Rahman, Muhammad Fuad (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
ARMA is a comfortable and durable rocking chair designed with a combination of modular system, and embedded with living animals and living plants. This bench designed for users to socialised while being accompany by natural living elements. The purpose of the aquarium or a terrarium is as starting topic for making conversation. Users can talk about what kind of fish, sharing their knowledge and many more. The aims of this design allow users to communicate and interact with other people. For introverts, the natural living elements can encourage a connection between them (but it still depends on their preferences towards the living things, as Introverts can be biophobic as well). Based on researches humans tend to experience, reflect and bond with nature physically and mentally, and recent studies have proven the benefits of nature in the built environment for people's health and avoid wellbeing nearby natural elements can promote relaxation, depression and make people behave, emotionally and mentally